2015
DOI: 10.3389/fpls.2015.01089
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Response of an Alpine Plant, Rhododendron delavayi Franch, to Water Stress and Recovery: The Role of Mesophyll Conductance

Abstract: Rhododendron delavayi Franch is an evergreen shrub or small tree with large scarlet flowers that makes it highly attractive as an ornamental species. The species is native to southwest China and southeast Asia, especially the Himalayan region, showing good adaptability, and tolerance to drought. To understand the water stress coping mechanisms of R. delavayi, we analyzed the plant's photosynthetic performance during water stress and recovery. In particular, we looked at the regulation of stomatal (gs) and meso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 54 publications
4
15
0
1
Order By: Relevance
“…Several previous studies have suggested that leaf photochemistry is relatively stable under water stress (Shabala & Pang, 2007;Flexas et al, 2009), as declines in PSII photochemistry occur at lower water contents than g s and TLP (Boyer & Potter, 1973;Miyashita et al, 2005). Moreover, significant declines in F v /F m occur after the complete loss of midrib xylem hydraulic function in sunflower plants (Cardoso et al, 2018). We importantly extended these findings showing…”
Section: Thresholds Of F V /F M Decline and Its Lack Of Post-dehydratsupporting
confidence: 79%
See 1 more Smart Citation
“…Several previous studies have suggested that leaf photochemistry is relatively stable under water stress (Shabala & Pang, 2007;Flexas et al, 2009), as declines in PSII photochemistry occur at lower water contents than g s and TLP (Boyer & Potter, 1973;Miyashita et al, 2005). Moreover, significant declines in F v /F m occur after the complete loss of midrib xylem hydraulic function in sunflower plants (Cardoso et al, 2018). We importantly extended these findings showing…”
Section: Thresholds Of F V /F M Decline and Its Lack Of Post-dehydratsupporting
confidence: 79%
“…Several studies have shown that stomatal pores reopen after plant rehydration, and reopening is associated with the recovery of K leaf and gas exchange (Miyashita et al, 2005;Blackman et al, 2009;Brodribb & Cochard, 2009;Martorell et al, 2014;Cai et al, 2015;Li et al, 2016;Skelton et al, 2017b). However, in contrast to g s , there may be limited recovery of photochemistry and mesophyll conductance after rehydration, which constrain full recovery of overall photosynthetic rate (Miyashita et al, 2005;Galm es et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…(2011), Han (), Jin et al (), Whitehead et al (), Xu and Zhou et al . (2011), Peguero‐Pina et al (, ,b), Tosens et al (,b, ), Varone et al (), Cano et al (), Martins et al (, ), TomĂ s et al (, ), Battie‐Laclau et al (), Brito et al (), Hommel et al (), ThĂ©roux‐Rancourt et al (), Bazihina et al (), Benomar et al (), Cai et al (), CarriquĂ­ et al (, ,b), Kitao et al (), Lima‐Nieto et al (), Mizokami et al (), Shi et al (), Xiong et al (, , ), Dong et al (), Fini et al (), Huang et al (), Jaikumar et al (), Lu et al (), Medeiros et al (), Veromann‐JĂŒrgenson et al (), Nadal et al () and Yang et al (). The two extreme lines of the boxplot ( whiskers ) show the 10 and 90% percentiles, the two boundaries of the box the 25 and 75% percentiles, and the centre thick line the median.…”
Section: Photosynthetic Capacity and Photosynthetic Efficiencies Alonunclassified
“…Correlation between V cmax and J max at 20–25°C modelled from A/C i curves from Arctic/alpine (blue diamond), warm desert (red square) and temperate (orange triangle) species. Data were compiled from Rogers et al (), Albert et al (), Cai et al (), Fan et al (), Shi et al (), Hamerlynck et al (), Huxman and Smith (), Shi et al (), Utsugi et al (), Hinojo‐Hinojo et al () and Kattge and Knorr (). Only statistically significant linear correlations for each group of species are shown.…”
Section: Photosynthesis In Extreme Environments: Taking Advantage Of mentioning
confidence: 99%